Hydroxyl Radical Scavenging Activity of Stachytarpheta jamaecensis Root Extract using In Vitro Deoxyribose Degradation Assay - Juliyatin Putri Utami; Yusrinie Wasiaturrahmah; Deby Kania Tri Putri (Faculty of Pharmacy, Universitas Gadjah Mada, 2021)
Use and demand of traditional medicinal plants currently growing in the direction that research in traditional medicines have also increased. One of the plants that is efficacious as a medicine is S. jamaecensis. This plant is usually used by people as a traditional medicine to treat various diseases. This study aims to determine the antioxidant activity of porterweed root. Antioxidant activity assays performed using hydroxyl radical scavenger that begins with the extraction by maceration. Dry roots of S. jamaecensis (250 g) was soaked with ethanol 96% for 3x24 hours at room temperature. The liquid extract obtained is evaporated by rotary evaporator and waterbath till viscous extracts is obtained. Then to extract performed phytochemical screening by quantitative and qualitative method. The antioxidant test was carried out using the hydroxyl radical scavenger method. The extract concentrations were varied, namely 125, 250, 500 and 1000 ppm. The data obtained was performed one-way ANOVA test. The results of the phytochemical screening showed the extract contains flavonoids, alcaloids, saponins, phenols and tannins. The results obtained were significant values from the antioxidant test with the antiradical scavenger method, the largest average value of root extract was 60.606% at a concentration of 1000 ppm. The results of spectrophotometric measurements showed that the extract has IC50 was 683.5294 µg/ml, while vitamin C has IC50 lower value (251.700 µg/ml). Q